Effect of Ab interno XEN gel stent implantation on corneal astigmatism - Pawasoot Supasai; Kanwasee Kanjana; Kannawee Boonchuenchom; Yosanan Yospaiboon (PLoS ONE, 2025)
Purpose To assess surgically induced astigmatism (SIA) after XEN gel stent implantation over 5 visits during a 3-month follow-up. Changes in intraocular pressure (IOP), IOP-lowering medications, and best-corrected visual acuity (BCVA) were also assessed. Methods This prospective cohort study recruited 24 eyes from 24 glaucoma patients at KKU Eye Center, Khon Kaen University, Thailand. All eyes underwent XEN implantation, using our specific surgical technique. We evaluated both the magnitude and the axis of SIA at 1, 2 weeks, 1, 2 and 3 months after the procedure. Preoperative and postoperative intraocular pressure (IOP), IOP-lowering medications, and best-corrected visual acuity (BCVA) were also analyzed. Results We observed a statistically significant centroid SIA of 0.14 D. at an axis of 105° and median SIA of 0.36 D. at 1 week following XEN (p < 0.01). However, no further significant statistical change in SIA was found at 2 weeks, and 1, 2, and 3 months postoperatively. Additionally, there was no significant change in BCVA after XEN. Moreover, reductions in IOP and IOP-lowering medications were statistically significant. Conclusions Ab Interno XEN gel stent implantation induces a small SIA immediately after the surgery, but no further significant change during 3-month follow-up period. Although SIA has no significant effect on visual acuity, this should be addressed with patients preoperatively. Further studies are needed to investigate how different surgical techniques may affect refractive changes after XEN.